(untitled) (Damascus University Journal of agriculture sciences, 2026)
This research investigated Cobalt’s seasonal and spatial distribution in the groundwater of 19 wells in Akkar Plain, Tartous Governorate, Syria. Spatial analysis revealed that Agricultural Well 1 had the highest Cobalt concentration in the groundwater, with an average value of 0.107 mg/L. Conversely, the Karto 1 well had the lowest concentration at 0.054 mg/L. The temporal analysis demonstrated that Cobalt concentrations were higher in spring than in autumn, with average values of 0.085 mg/L in spring and 0.075 mg/L in autumn. Of the four seasons, spring 2019 had the highest average Cobalt concentration at 0.141 mg/L, while spring 2020 had the lowest at 0.03 mg/L. The variance distribution test indicated that the season factor was the most significant factor affecting the variance of Cobalt distribution among the studied factors (replicates, season, site, site*season). The excessive use of fertilizers is believed to be the main cause of Cobalt distribution in the groundwater. Other contributing factors include untreated sewage sludge, irrigation from Cobalt-contaminated water bodies, and the high levels of this metal in soils, either naturally or due to agricultural activities. All of these factors have led to an increase in Cobalt concentrations in the groundwater. Groundwater Cobalt distribution in Akkar Plain decreased significantly during spring 2020 due to COVID-19 quarantine, highlighting human impact. Thematic maps and statistical studies have shown that the distribution of Cobalt in the groundwater of Akkar Plain is widespread. The majority of the results indicate that the levels of Cobalt exceed the permissible limit for drinking water of 0.05 mg/L.